2021
DOI: 10.1103/physrevlett.126.094802
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of an Electrostatic Orbital Angular Momentum Sorter for Electron Beams

Abstract: We report the first experimental demonstration of an electrostatic electron orbital angular momentum (OAM) sorter, which can be used to analyze the OAM states of electrons in a transmission electron microscope. We verify the sorter functionality for several electron beams possessing different superpositions of OAM states, and use it to record the electron beams OAM spectra. Our current electrostatic OAM sorter has an OAM resolution of 2 in the units of ℏ -the reduced Planck constant. It is expected to increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…They suggested to improve the effectiveness of their sorter by substituting the holograms with electrostatic fields to reduce absorption. In 2021, Tavabi et al 61 demonstrated such an electrostatic sorter.…”
Section: Applicationsmentioning
confidence: 99%
“…They suggested to improve the effectiveness of their sorter by substituting the holograms with electrostatic fields to reduce absorption. In 2021, Tavabi et al 61 demonstrated such an electrostatic sorter.…”
Section: Applicationsmentioning
confidence: 99%
“…While space representation is the one most commonly used, other representations could be more appropriate. One typical example is the angular basis, which includes the radial degree of freedom and orbital angular momentum (OAM) of the electron beam (Verbeeck et al, 2010;McMorran et al, 2011;Grillo et al, 2017;Tavabi et al, 2021), and allows one to improve the efficiency of the measurement by increasing the amount of information that can be accessed in the measurement.…”
Section: Quantum Sortermentioning
confidence: 99%
“…Figure 6 represents the scheme of the electron microscope in the special configuration able to change the representation from a Cartesian to an angular basis. The device has already been demonstrated experimentally (Tavabi et al, 2021). Two coupled phase holograms or two equivalent electrostatic phase elements are placed in the microscope.…”
Section: Quantum Sortermentioning
confidence: 99%
“…One of the most significant recent developments is electron beam shaping through electron optical components based on microelectromechanical systems technology [4] that can be used to generate vortex beams [5], non-diffracting beams [6], compact aberration correctors [7] and quantum state analysers [8].…”
Section: Modena Modena Emilia-romagna United Statesmentioning
confidence: 99%